Tradisi Ruwatan Pada Prespektif Islam Masyarakat Demak Jawa Tengah - Fadlilah, Niah Dian; Rodiyah, Afifatur; Wulandari, Nisrina; Farhan Erdianto, Muhammad; Faiz Arya Yudhanta, Mochammad; Muhammad Noor, Aditia (Universitas Nahdlatul Ulama Sunan Giri, 2024)
Java is one of the largest tribes in Indonesia which has a variety of customs. The Javanese are closely related to supernatural beliefs or what is often known as belief in the Spiritual realm. Javanese people have various concepts that are used as songs that carry out a traditional ceremony. Traditional ceremonies carried out to get away from influences caused by human mistakes and carelessness, this culture in Java is called ruwatan. Ruwatan culture is a form of traditional ritual for self-cleaning which is still upheld today as the original tradition of the people of Demak, Central Java. The ruwatan ceremony is an acculturation tradition which also comes from the teachings of Kanjeng Sunan Kalijaga and is needed for people who are Nandang Sukerta or are in sin. This tradition is celebrated every year by witnessing the devotion to the ancestors and glorification of the Almighty. The presence of this cultural ritual of Ruwatan Bumi has philosophical points that can be observed from the procession and the equipment that will be used, among others, enthusiasm, hard work, gratitude for the blessings bestowed by the Almighty, devotion to the ancestors. Ruwatan can mean transcending or eliminating an inner misery by carrying out a ceremony or ritual. This culture is needed as a source of teaching local history, because of the historical insight that exists in the ruwatan tradition. The purpose of this analysis is to find out the process of knowing the ngruwat ceremony, the process of Islamization of the ngruwat tradition, and the influence of the ngruwat tradition on social culture and community life. The research method applied uses qualitative methods that examine journals and other literature.